Activity and habitat use of two species of stingrays (Myliobatiformes: Potamotrygonidae) in the upper Parana River basin, Southeastern Brazil - Garrone Neto, Domingos [UNESP]; Uieda, Virginia Sanches [UNESP] (Soc Brasileira Ictiologia, 2012)
The life history of freshwater stingrays (Potamotrygonidae) under natural conditions has been poorly documented. In this study, we investigated the period of activity and the habitat use of two species of the genus Potamotrygon in the upper Parana River basin, Southeastern Brazil. Potamotrygon falkneri and P. motoro are similar to each other as far as the analyzed behavior is concerned. Individuals of both species segregate according to their size, and in function of the depth and period of the day. Younger individuals inhabit mostly sandy beaches and places that are no deeper than four meters throughout the whole day. Bigger stingrays realize bathymetric migrations, alternating their position between places deeper than eight meters during the day, and shallow areas at night. Individuals of intermediate size inhabit transition environments that have greater habitat diversity. Both species presented mostly nocturnal habits, especially regarding their feeding behavior. The behavioral patterns observed seem to go through ontogenetic variations and probably change throughout the year, between dry and wet seasons.
Keywords: Bathymetric migration; Dial movements; Potamotrygon; Scientific diving; Spatial ecology